2014
DOI: 10.1111/famp.12062
|View full text |Cite
|
Sign up to set email alerts
|

Stepparents and Parenting Stress: The Roles of Gender, Marital Quality, and Views about Gender Roles

Abstract: Previous research suggests that stepparenting can be stressful, although the mechanisms that contribute to the experience of parenting stress in stepfamilies are less clear. This study examines gender, marital quality, and views about gendered family roles as correlates of parenting stress among 310 stepmothers, stepfathers, and biological mothers and fathers. Findings suggest that stepparents, and especially stepmothers, experience higher levels of parenting stress than biological parents. Findings also sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 64 publications
2
32
0
1
Order By: Relevance
“…Only those surveys in which both partners provided information were considered for this study. In addition, as there were very few stepparents in our sample (less than 2%), and because stepparents' parenting roles are more complex and less defined than biological parenting roles (Shapiro, 2014), we eliminated these parent-stepparent pairs and only retained in the final sample those participants who were their child's biological parents. The parents' participation rate was 38%.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Only those surveys in which both partners provided information were considered for this study. In addition, as there were very few stepparents in our sample (less than 2%), and because stepparents' parenting roles are more complex and less defined than biological parenting roles (Shapiro, 2014), we eliminated these parent-stepparent pairs and only retained in the final sample those participants who were their child's biological parents. The parents' participation rate was 38%.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Researchers have noted the need to approach studies of stepfamilies from a family systems perspective in order to develop a better understanding of these complex family processes (Dupuis, 2010; Shapiro, 2014). Because family members are interconnected, and not simply a compilation of individual relationships, research that examines the manner in which subsystems impact each other may offer greater insight in understanding their influence on individual well-being (Higginbotham et al, 2012; Jensen & Shafer, 2013; Schrodt et al, 2008).…”
Section: Stepfather-stepchild Relationship Qualitymentioning
confidence: 99%
“…In general, married African Americans tend to report low levels of marital quality (e.g., Broman, 2005; Bulanda & Brown, 2007). High overall marital quality helps stepparents adjust better to their new parenting role (Shapiro, 2014) and contributes to positive mental health outcomes for stepparents (Shapiro & Stewart, 2012). The present study contributes to the current literature by considering multiple indicators of marital quality within the context of African American stepfamilies.…”
Section: Marital Quality and Interactions As Mediatorsmentioning
confidence: 99%
“…Several studies on stepparents and biological parents have shown that difficulties during the family formation process can easily occur in stepfamilies, and particularly for stepmothers, who experience higher stress levels [5–8]. These findings accord with stepfamily research in Western societies [911]. In addition, several studies have shown that residing in a stepfamily is a risk factor for child abuse [12, 13].…”
Section: Introductionmentioning
confidence: 72%
“…In contrast, having low levels of traditional gender role perceptions is reported to function as a protective factor in stepfamily mothers’ mental health [11]. Thus, professionals need to consider the stepfamily mother’s place in her family based on a deep understanding of the difficulties surrounding stepfamily formation.…”
Section: Discussionmentioning
confidence: 99%